The Effect of Endurance Training on Brain-Derived Neurotrophic Factor and Inflammatory Markers in Healthy People and Parkinson's Disease. A Narrative Review - Małczyńska-Sims, Paulina; Chalimoniuk, Małgorzata; Sułek, Anna (Frontiers in Physiology, 2020)
Background: One purpose of the training conducted by people is to lose bodyweight and improve their physical condition. It is well-known that endurance training provides many positive changes in the body, not only those associated with current beauty standards. It also promotes biochemical changes such as a decreased inflammatory status, memory improvements through increased brain-derived neurotrophic factor levels, and reduced stress hormone levels. The positive effects of training may provide a novel solution for people with Parkinson's disease, as a way to reduce the inflammatory status and decrease neurodegeneration through stimulation of neuroplasticity and improved motor conditions. Aim: This narrative review aims to focus on the relationship between an acute bout of endurance exercise, endurance training (continuous and interval), brain-derived neurotrophic factor and inflammatory status in the three subject groups (young adults, older adult, and patients with Parkinson's disease), and to review the current state of knowledge about the possible causes of the differences in brain-derived neurotrophic factor and inflammatory status response to a bout of endurance exercise and endurance training. Furthermore, short practical recommendations for PD patients were formulated for improving the efficacy of the training process during rehabilitation. Methods: A narrative review was performed following an electronic search of the database PubMed/Medline and Web of Science for English-language articles between January 2010 and January 2020. Results: Analysis of the available publications with partial results revealed (1) a possible connection between the brain-derived neurotrophic factor level and inflammatory status, and (2) a more beneficial influence of endurance training compared with acute bouts of endurance exercise. Conclusion: Despite the lack of direct evidence, the results from studies show that endurance training may have a positive effect on inflammatory status and brain-derived neurotrophic factor levels. Introducing endurance training as part of the rehabilitation in Parkinson's disease might provide benefits for patients in addition to pharmacological therapy supplementation.